ANALISIS PENGARUH STABILITAS KEUANGAN DAN TEKANAN EKSTERNAL TERHADAP KECURANGAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Sub Sektor Otomotif yang terdaftar di Bursa Efek Indonesia tahun 2015 - 2018) - Ismiani Aulia; Kiki Fatmala; Azzahra Hani Putri; Adhaliah Pratiwi; Agi Pranata Muslim; Gusganda Suria Manda (STKIP Pembangunan Indonesia Makassar, 2020)
This study aims to determine influence financial stability (X1), and external pressure (X2)to the fraudulent financial statements (Y) at automotive subsector companies listed in IndonesianStock Exchange (IDX) of the year 2015-2018. The samples were 12 companies from 12 of totalpopulation using purpossive sampling method. The analytical method used in this study is multiplelinear regression. The result of this show that: financial stability (1) has not effect on fraudulentfinancial statements, external pressure (2) has not effect on fraudulent financial statements.Key word: financial stability, external pressure, and fraudulent financial statements